The Effect of Internal Communication and Teamwork on the Performance of the Student Organization Board at Ar-Raudlatul Hasanah Islamic Boarding School in Medan - Faisal, Harik Aziz; Hulu, M. Rizki Hanif; Jannah, Miftahul; Hamdan, Al-Hafizh Mubarak (Universitas Dharmawangsa Medan, 2025)
This study aims to determine the effect of internal communication and team collaboration on the performance of the student organization board at Ar-Raudlatul Hasanah Islamic Boarding School in Medan. A descriptive quantitative research design was employed. The population comprised the active board members of the student organization at Ar-Raudlatul Hasanah. A purposive sampling technique was applied, yielding a total sample of 125 respondents. Data were collected through a structured questionnaire and analyzed using simple linear regression, multiple linear regression, t-tests, F-tests, and the coefficient of determination. The findings reveal that internal communication does not have a statistically significant partial effect on the performance of the student organization board. In contrast, team collaboration exhibits a positive and significant partial influence on board performance. Furthermore, internal communication and team collaboration collectively have a positive and statistically significant simultaneous impact on the performance of the student organization board at Ar-Raudlatul Hasanah Islamic Boarding School, Medan.